Study of occlusal acoustic parameters in assessing masticatory performance - Yue Xia; Lu Wang (BMC, 2022)
Abstract Background Previous masticatory studies have focused on a variety of measurements of foods and boluses or kinematic parameters and sound during mastication. To date, the masticatory sound research of has been limited due to the difficulties of sound collection and accurate analysis. Therefore, significant progress in masticatory sound has not been made. Meanwhile, the correlation between acoustic parameters and mastication performance remains unclear. For the purpose of exploring the acoustic parameters in measuring mastication performance, the bone-conduction techniques and sound analysis were used, and a statistical analysis of acoustic and occlusal parameters were conducted. Methods The gnathosonic and chewing sounds of fifty-six volunteers with healthy dentate were recorded by a bone-conduction microphone and further analyzed by Praat 5.4.04 when intercuspally occluding natural foods (peanuts) were consumed. The granulometry of the expectorated boluses from the peanuts was characterized by the median particle size of the whole chewing sequence (D50a) and the median particle size during the fixed chewing strokes (D50b). The chewing time of the whole chewing sequence (CTa), the chewing time of the fixed chewing strokes (CTb), the chewing cycles (CC), and the chewing frequency (CF) were recorded and analyzed by the acoustic software. The acoustic parameters, including gnathosonic pitch, gnathosonic intensity, mastication sound pitch of the whole chewing sequence (MPa), mastication sound pitch of the fixed chewing strokes (MPb), mastication sound intensity of the whole chewing sequence (MIa) and mastication sound intensity of the fixed chewing strokes (MIb), were analyzed. Independent sample t-test, Spearman and Pearson correlation analyses were used where applicable. Results Significant difference in parameters CC, MIa, CF and D50a were found by sex (t-test, p < 0.01). The masticatory degree of the test foods was higher in women (CC, 24.25 ± 5.23; CF, 1.70 ± 0.21 s−1; D50a, 1655.07 ± 346.21 μm) than in men (CC, 18.14 ± 6.38; CF, 1.48 ± 0.18 s−1; D50a, 2159.21 ± 441.26 μm). In the whole chewing sequence study, a highly negative correlation was found between MIa and D50a, and a highly positive correlation was found between MIa and CF (r =  − 0.94, r = 0.82, respectively, p < 0.01). No significant correlation was found between the remaining acoustic parameters and mastication parameters. In the fixed chewing strokes study, a highly negative correlation was found between MIb and D50b (r =  − 0.85, p < 0.01). There was no significant correlation between the rest of the acoustic parameters and the mastication parameters. Conclusions Mastication sound intensity may be a valuable indicator for assessing mastication. Acoustic analysis can provide a more convenient and quick method of assessing mastication performance.